Effect of Torso and Breast Characteristics on the Perceived Fit of Body Armour Systems Among Female Soldiers: Implications for Body Armour Sizing and Design - Coltman, Celeste E.; Brisbine, Brooke R.; Molloy, Richard H.; Steele, Julie R. (Frontiers in Sports and Active Living, 2022)
This study aimed to provide normative data characterising the torsos and breasts of female soldiers and to determine which torso and breast anthropometric measurements contributed to reports of poor body armour fit. Ninety-seven female Australian Army soldiers completed a questionnaire about their experience with current-issue body armour, including perceptions of fit. Participants also attended a single testing session where we took a three-dimensional scan of their breasts and torso and collected several anthropometric measurements to characterise their torso size and shape. Sixteen of the 22 breast and torso measurements collected were significantly related to the perceived fit of current-issue body armour systems. To improve perceptions of fit for female soldiers and, in turn, reduce movement interference, discomfort, and barriers to occupational performance, future body armour systems should cater to the wide range of female breast and torso shapes and sizes.